PENERAPAN SYARI’AH DI NEGARA MODERN (Analisis Ijtihad Pemikiran Abdullahi Ahmed An-Na’im) - Ahmad Bahrur Rozi (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2015)
Islam is a holistic religion. It means that Islam is a religion which does not only focus on the vertical relation between humans and God but also contains rules of horizontal relation between man and man. Laws with social characteristic lead to the existence of a power as the doer, such as the application of all the punishments and public rewards (al-hudûd wa al-'uqûbât). This article analyzes the thought of Abdullahi Ahmed An--Na’im about syari’ah reformation which is relevant to the constitutionalism standard, criminal law, international law and modern human right, a vision of “syariat modern” which is suitable with the nation state concept which beyond  the offering of the Nation of fundamentalist syariah and the offering of Modern Islamic Nation. The method used by Abdullahi Ahmed An--Na’im is the renewal method which is said as legalized evolution with hermeneutic as the main tool to reach the purpose and normative implication of the text as al-Qur’an. According to Abdullahi Ahmed An--Na’im, the failure of syari’ah application in modern country caused by the crisis on the traditional syari’ah methodology which became its base. Therefore, new syari’ah formulation is needed to be built on the new base. Naskh concept which is initiated by An-Na’im is for answering this crisis.Copyright (c) 2016 by Al-Ihkam. All right reservedDOI: 10.19105/al-ihkam.v10i2.734